Tatak Pilipino [episode no. 13]. ([Quezon City ABS-CBN, 1991)
A uniquely Pilipino way and style.
Trece : lucky of unlucky number> (5 min.) -- Kissing with the nose (5 min.) -- Motels (15 min.) -- Love story of two couples (i.1. Tinios feature) (15 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Thirteen (The Number).; Number, Cardinal; Courtship -- Philippines; Kissing; Motels -- Philippines; Love stories